Determinanty i typy karier zawodowych a osiągnięcie sukcesu - Smolbik-Jęczmień, Alicja (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This study presents the issues of factors determining career development of employees and types of career in achieving success by an individual as well as by an organization. A special attention was paid to the following issues: specific initial conditions of career, mainly psychosocial ones, optimal life and career decisions based on the right criteria, D. Super's career development theoretical concepts, Holland's personality and need theoretical concepts, and E.M. Schein's career anchor concepts. The study also includes some research findings regarding issues presented in the article. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 332-338